EDUCATIONAL OPPORTUNITIES OF COLLAGE AS A DIDACTIC MEANS: INTERDISCIPLINARY APPROACH - I. B. Ryzhkina (Obrazovanie i Nauka)
The research aim is to examine the functions and educational opportunities of collage as a didactic means.The methodology and methods involve the multilateral theoretical data analysis and generalization; activity approach to pupils’ perception analysis; communicative approach to finding the interrelation between the perception and speech act; lingua-cultural approach to collage consideration as a sign, information vehicle and communication subject; and developmental teaching approach.The author undertakes the cross-disciplinary analysis, including the scientific works on philosophy, psychology, semiotics and culture studies, and proves the collage adequacy to the cognitive specificity of modern pupils’perception and foreign-language teaching. The concept of collage is specified, its semiotic characteristics and unique features as a didactic means discussed.The research novelty involves developing a new frame of reference to collage as a didactic tool and cultural phenomenon with educational and developmental opportunities.The research findings, including the methodology basis for content structuring and selecting a collage type, can be used for educational problem solving.